FRI0518 Ultrasound Definitions for Vasculitis in Cranial and Large Vessel Giant Cell Arteritis: Results of A Delphi Survey of The Omeract Ultrasound Large Vessel Vasculitis Group. (15th July 2016) - Duftner, C.; Dejaco, C.; Moller Dohn, U.; Bruyn, G.A.; Chrysidis, S.; D'Agostino, M.A.; Dasgupta, B.; de Miguel, E.; Diamantopoulos, A.P.; Hanova, P.; Hartung, W.; Iagnocco, A.; et al.
Abstract : Background: In a systematic literature review (SLR), we identified halo sign, stenosis, occlusion, compression sign and a decreased vessel wall pulsation as elementary ultrasound (US) lesions in giant cell arteritis (GCA). Objectives: To establish consensus-based definitions for the key elementary US lesions in GCA. Methods: We invited 25 rheumatologists from 13 countries experienced in musculoskeletal and vascular US to participate in a Delphi exercise. Based on the results from the SLR and international expert consensus a questionnaire was developed including 12 statements on the definitions of normal temporal and extra-cranial large arteries, arteriosclerosis, halo sign, stenosis, occlusion, compression sign, and vessel wall pulsation. The experts were asked to express their level of agreement or disagreement with the proposed statements. A consensus was defined as agreement of ≥75% of participants. Results: The response rate was 24/25 (96%) in round 1 and 24/24 (100%) in round 2. A consensus was achieved for 9/9 Delphi statements [normal temporal and extra-cranial large arteries, arteriosclerosis, halo sign, stenosis of temporal and extra-cranial large arteries, occlusion, compression sign (temporal arteries), US assessment of compression sign (temporal arteries) in round 1. In round 2, 3/3 Delphi statements (arteriosclerosis, halo sign, stenosis of temporal arteries) were redefined. The statements on vessel wall pulsation (definition and assessment) and measurement of vessel wall thickness did not reach the threshold for consensus. The halo and compression signs were deemed to be the most important US signs for GCA with 100% and 83.3% expert agreement, respectively. Conclusions: This is the first international consensus on definitions for elementary US lesions in GCA. The next steps of the OMERACT project will be web- and patients based exercises testing the reliability of the new definitions. Disclosure of Interest: None declared